烘烤温度对浓香油莎豆油风味及综合品质的影响Effects of roasting temperature on the flavor and comprehensive quality of fragrant Cyperus esculentus oil - 陈璐1，刘玉兰1，朱文学1，马宇翔1，王会伟2，李春鑫2 CHEN Lu1, LIU Yulan1,ZHU Wenxue1,MA Yuxiang1, WANG Huiwei2,LI Chunxin2 (Zhongguo youzhi, 2022)
在浓香型油脂的生产中油料烘烤温度是影响产品风味的重要因素，为了对浓香油莎豆油的产品开发和工艺条件优化提供支持，采用不同温度对油莎豆进行烘烤并压榨制取浓香油莎豆油，对油莎豆油的多个品质指标进行检测分析，明确烘烤温度对油莎豆油风味及综合品质的影响。结果表明：油莎豆经140、150、160、170、180 ℃烘烤25 min后榨取的5个油样的酸值（KOH）为1.36～2.31 mg/g，过氧化值为1.60～2.24 mmol/kg，维生素E含量为177.82～207.14 mg/kg，甾醇含量为20873～230.01 mg/100 g；烘烤温度对油莎豆油的脂肪酸组成影响不大，但随温度升高反式脂肪酸含量从未检出升高至0.029%，3,4-苯并\[a\]芘（BaP）含量从1.06 μg/kg升高至1.66 μg/kg，多环芳烃（PAH16）含量从63.67 μg/kg升高至72.50 μg/kg，3-氯丙醇酯均未检出；随烘烤温度升高，5个油样中挥发性成分的种类及含量分别为60种16.46 mg/kg、87种33.07 mg/kg、81种22.36 mg/kg、78种17.71 mg/kg、57种21.78 mg/kg；150 ℃ 烘烤时油莎豆油的挥发性成分的种类和含量最为丰富；赋予浓香油莎豆油烘焙坚果味等正面风味属性的主要为杂环类物质，包括2,5-二甲基吡嗪和2-正戊基呋喃，其中2,5-二甲基吡嗪在140 ℃时的油莎豆油中未检出，之后随烘烤温度升高，在杂环类物质中的占比从烘烤温度150 ℃时的24.16%升高至烘烤温度为180 ℃的34.06%。综合油莎豆油风味、安全品质、营养品质和质量指标，浓香油莎豆油生产中以烘烤温度不超过 160 ℃、烘烤时间不超过 25 min 为佳。 The roasting temperature of oilseeds is an important factor affecting the flavor of the product in the production of fragrant oil. In order to provide support for the product development and process optimization of fragrant Cyperus esculentus oil, the Cyperus esculentus was roasted under different temperature, and then pressed to prepare fragrant Cyperus esculentus oil. Multiple physicochemical indexes of pressed Cyperus esculentus oil were detected and analyzed to clear the effects of roasting temperature on the flavor and comprehensive quality of Cyperus esculentus oil. The results indicated that five Cyperus esculentus oil samples were extracted after roasting at 140,150,160,170,180 ℃ for 25 min had acid values of 1.36-231 mgKOH/g and peroxide values of 1.60-2.24 mmol/kg. The vitamin E and sterol contents were 177.82-20714 mg/kg and 208.73-230.01 mg/100 g, respectively. The fatty acid composition of Cyperus esculentusoil was not significantly affected by roasting temperature, but the trans-fatty acid content increased from undetectable to 0.029%, and 3,4-benzo\[a\]pyrene (BaP) content increased from 1.06 μg/kg to 1.66 μg/kg. The content of polycyclic aromatic hydrocarbons (PAH16) increased from 63.67 μg/kg to 72.50 μg/kg, and 3-chloro-1,2-propanediol ester was not detected. The types and contents of volatile components in the five oil samples were 60 kinds of 16.46 mg/kg, 87 kinds of 33.07 mg/kg, 81 kinds of 22.36 mg/kg, 78 kinds of 17.71 mg/kg, and 57 kinds of 21.78 mg/kg, respectively. The most abundant volatile components were found in the oil extracted from the Cyperus esculentus roasted at 150 ℃. The positive flavor attributes of the Cyperus esculentus oil with the roasted nutty flavor were mainly attributed to heterocyclic substances, including 2,5-dimethylpyrazine and 2-pentylfuran. The 2,5-dimethylpyrazine were not detected in the oil roasted at 140 ℃, and then increased from 24.16% at 150 ℃ to 34.06% at 180 ℃. According to the flavor, safety quality, nutritional quality and quality indicators, it is better that the roasting temperature should not exceed 160 ℃ and the roasting time should not exceed 25 min in the production of fragrant Cyperus esculentus oil.